Martial Arts and ADHD: A Narrative Review of Cognitive, Behavioral, and Epigenetic Effects - Carola Costanza; Francesco Paolo Colecchia; Rita Polito; Marcellino Monda; Marco Carotenuto; Giovanni Messina; Antonietta Monda; Nicola Mancini; Fiorenzo Moscatelli; Giuditta Bargiacchi; Maria Ruberto (Physical Education Theory and Methodology)
Objectives. The study aimed to explore the cognitive, behavioral, and potential epigenetic effects of martial arts-based interventions in individuals with Attention-Deficit/Hyperactivity Disorder (ADHD).